Proyecto de factibilidad para la producción y comercialización de jabón líquido con esencia a maracuyá en la ciudad de Loja - Gutiérrez Tene, Luis Miguel (2018)
This research work was developed in the city of Loja, with the main purpose of presenting a proposal to implement a project for the production and commercialization of liquid soap with passion fruit essence, this new product being an excellent alternative in the market for its quality and price, which allowed to establish favorable conditions for its implementation and start-up. As for the proposed objectives, these were met through the realization of a diagnosis of the types of existing liquid soaps (brands, prices, presentations, fragrances, etc.); a market study was carried out to determine the supply and demand of the liquid soap product with passion fruit essence in the city of Loja and to establish its marketing strategies; then a technical study was carried out to determine the capacity of production in the company and the engineering of the project; likewise in the organizational study the company was structured in its legal and functional part, with its organizational charts and the manual of functions for each job, finally in the financial study the costs and expenses were structured in which it will be incurred through the implementation of the project and during its useful life and the financial evaluation was carried out to establish the profitability and feasibility that the project will have at the time of its implementation. Within the results obtained in the Market Study, a number of 180,617 inhabitants was obtained, which are concentrated in the urban area of the city of Loja; where the potential demand was determined that 58.69% uses liquid soap; Real demand 84% would include the new product; and as for the acquisition of the new liquid soap product with passion fruit essence, it was obtained that 73% would buy it; what represents the effective demand of the project; while the Unsatisfied Demand is 128,204 liters. In reference to the Technical Study, the technological component, the 5 physical structure, the distribution of the plant, the production process, the location, the Designed capacity that is 295,650 units of 500ml, the Installed Capacity that is 35,100 units of 500ml and a Used capacity of 35,100 units of 500ml. For the execution of the project an investment of $ 31.717,58 is required; which will be financed 52,71 % by the owner of the company and 47,29% by a financial entity BanEcuador; the cost of the product will be $ 3,65 for each 500ml unit. The Financial Evaluation determined: the net present Value that is $ 102.329; the Internal Rate of return is 56,88%, in the Benefit Cost Ratio the profit will be 0.31 cents for each dollar invested; The Capital Recovery Period is 2 years, 6 months and 21 days, the Sensitivity Analysis with an increase in costs of 11,45%; and with the decrease in income of 9,10%. Finally, it is concluded that the project is feasible and it is recommended to put it into practice.